The effect of mountaineering on the grit of college students: an empirical study - Lun Li; ZuWang Chu; FuLin Li; JiaoJiao Li; Kang Wang; Yun Zhou (PeerJ)
Objective Although ample evidence in the literature suggests a correlation between general sports participation and resilience, information on the potential impact of specific sports activities on resilience is lacking. Therefore, we attempt to evaluate the effect of mountaineering on the grit of college students. Methods The study recruited 12 healthy college students for a three-day mountaineering activity. Then, the grit scores of the students before and after mountaineering were tested using the Chinese version of the original grit scale (Grit-O). During the mountaineering process, the oxygen saturation of the subjects was measured and recorded using a portable finger clipper. The scores of the Lake Louise Scale (2018 Lake Louise Acute Mountain Sickness Score, LLS) were used to distinguish whether the mountaineers had acute mountain sickness (AMS). Independent t-tests and paired t-tests were performed on the data separately. Results A significant correlation exists between the total score of grit among college students before and after mountaineering (r = 0.646, Sig < 0.05). However, the total score did not significantly improve after mountaineering (p = 0.054), the effort scores of all college students increased significantly before and after mountaineering (p = 0.045). A significant correlation is also observed between the total score of grit among college students who have not suffered from AMS (r = 0.764, Sig < 0.05). However, no significant improvement occurs (p = 0.075). Meanwhile, no significant correlation exists between the efforts (r = 0.499, Sig > 0.05) and interests (r = 0.562, Sig > 0.05) of college students before and after mountaineering. AMS has no significant correlation with the resilience of college students before and after mountaineering, in terms of effort (r = 0.456, Sig > 0.05) and interest (r = 0.601, Sig > 0.05), while no significant difference was observed between the total resilience score, effort and interest of mountaineering and non-mountaineering college students before and after mountaineering (all p >  0.05). Conclusion In the short term, mountaineering has a certain enhancing effect on cultivating the grit of college students. However, the existing grit scale cannot fully reflect the resilience scores of mountaineers before and after. Hence, other situational dimensions should be added to the design of the grit scale.